Perladangan Padi Paya Suku Kantu di Kalimantan Barat - Michael Dove (Antropologi Indonesia, 1991)
Briefly, the author describes about swamp-rice swiddens of the Kantu' in the upper reaches of the Kapuas river valley, West Kalimantan. Besides the cultivation of dry-swiddens, the Kantu' can utilize swamp-land surrounding their place to increase their food because it result a quite high harvest. The return of per work-day in the swamp-swiddens compared with in the dry-swiddens is 11,3 liters/day with 9,7 liters/day. However, the other things more important are planning in the swamp-land relatively "safe" since only such land which is immune to the ever-present threat - along the river - of flooding, and the brief fallow periods just take 1,2 to 2,5 years.